PENGARUH iIKLAN iMEDIA iSOSIAL iINSTAGRAM iTERHADAP iKEPUTUSAN iPEMBELIAN iKOSMETIK iPADA iMAHASISWA iTATA iRIAS iDAN i KECANTIKAN FPP UNP - Vija Aida; Hayatunnufus Hayatunnufus (Universitas Negeri Padang, 2021)
This iresearch iis imotivated iby ithe idevelopment iof itechnology iin ithe i21st icentury iwhich iis icalled ithe iera iof idigitalization, inamely iany iform iof ihuman iactivity ican ibe idone ithrough idigital ithat irests ion ithe iinternet. iOne iform iof iinternet-based idigital iuse iis isocial imedia, iby iusing isocial imedia iusers ican ido ivarious iactivities isuch ias ipublishing iphotos iand idoing imarketing iby imeans iof ipromotion ior iadvertising, ione iof ithe isocial imedia iapplications ithat iare ioften iused ias iadvertising iplatforms iis iinstagram. iWith ithe iincreasing inumber iof isocial imedia iusers ifrom iyear ito iyear, ithis ibecomes ian iopportunity ifor imarketers iin iconducting itheir iproduct imarketing iprograms ithrough isocial imedia. iThis istudy iaims ito ifind iout iif iinstagram isocial imedia iads ihave ian ieffect iand ihow ithe iinfluence iof isocial imedia iads ion ithe idecision ito ipurchase icosmetics ion istudents iof iMakeup iand iBeauty iPadang iState iUniversity. iThis itype iof iresearch iis idescriptive iquantitative, ithe ipopulation iin ithis istudy iis istudents imajoring iin iMakeup iand iBeauty iPadang iState iUniversity iclass iof i2017 iand i2018 iwhich iamounted ito i207 ipeople, ithe isampling itechnique iis ipurposive isampling iwith ia itotal iof i67 ipeople. iData iretrieval iusing iquestionnaires i(questionnaires) ithat iare iadjusted iin ithe iform iof ilikert iscales ithat ihave ibeen itested ifor ivalidity iand ireliability. iData ianalysis itechniques iusing it itest iand icoefficient iof idetermination itest. iThe iresults ishowed ithat iinstagram isocial imedia iads ihad ia isignificant ieffect ion ithe idecision ito ipurchase icosmetics iin istudents iof iMakeup iand iBeauty iPadang iState iUniversity ias ievidenced iby ithe iresults iof ithe it itest iwhich iobtained ia ithitung ivalue iof i5,848. iThe ivalue i> ithe itable it ivalue iof i1,999. iFor ithe ivalue iof itable it ican ibe iseen iin ithe itable iof idistribution ivalues iwith ithe idejarat ifreedom i(dk) i0.025 inumber i64 iwhich iis i1,999. iSo iit ican ibe iinterpreted ithat iHo iwas irejected iHa iaccepted iwhich imeans isignificant. iAnd ithe ipercentage iof isocial imedia iadvertising iinfluence iinstagram ion ithe idecision ito ipurchase icosmetics iin istudents iof imakeup iand ibeauty iPadang iState iUniversity iis i0.569 (56.9%). iBased ion ithe iresults iof ithe iresearch iis isuggested ican ibe iused ito iadd iknowledge iand ilibrary imaterials, iespecially iabout isocial imedia iadvertising iinstagram iand ithe idecision ito ipurchase idecorative icosmetics ias iwell ias ia ireference ifor iyoung iwomen iand istudents iin ichoosing icosmetics.